Region of adaptive threshold segmentation between mean, median and otsu threshold for dental age assessment - Mohamed Razali M.R.; Ahmad N.S.; Mohd Zaki Z.; Ismail W. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus